If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15n + 2 = -13n + -8 Reorder the terms: 2 + -15n = -13n + -8 Reorder the terms: 2 + -15n = -8 + -13n Solving 2 + -15n = -8 + -13n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '13n' to each side of the equation. 2 + -15n + 13n = -8 + -13n + 13n Combine like terms: -15n + 13n = -2n 2 + -2n = -8 + -13n + 13n Combine like terms: -13n + 13n = 0 2 + -2n = -8 + 0 2 + -2n = -8 Add '-2' to each side of the equation. 2 + -2 + -2n = -8 + -2 Combine like terms: 2 + -2 = 0 0 + -2n = -8 + -2 -2n = -8 + -2 Combine like terms: -8 + -2 = -10 -2n = -10 Divide each side by '-2'. n = 5 Simplifying n = 5
| 7x+6=1x-6 | | (G+4)+-3g=1+g | | 5(P-1)=2P+8(P-1) | | -15n+2=-13n-18 | | 4(4x-3)=2(8x+4) | | 4-5+54= | | 7+2m-5=9m+9-6m | | 16x^2-4x^2=0 | | x-y^2=w^2 | | -36-7x=-4x+4(x-2) | | 4t+7t=19 | | 3.998=x^2-3x | | m-22=-14 | | v+5x=w | | -2-4*4+7*5= | | 6x-10+4=15-(9x-4) | | 25y-3=4 | | 2y^4-9y^2+1=0 | | 99+1.2= | | 27-3-(-8)= | | 2s+3s=40 | | 5x-4x=9 | | 9x+23=4x+123 | | 2x-3/3=2 | | 6*-4+5-3+8= | | 3-8v-5v^2=2v | | 4m^4+8m^3+8m^2+4m+1=0 | | ln(x^2+3x)=1.386 | | -5x^2+7x+20=0 | | 21-(-8)-4= | | -5+10=12x-3-11x | | 4a-5=2a-3 |